Why Ecclesiology Cannot Live By Doctrine Alone - Brittain, Christopher Craig (Ecclesial practices, 2014)
This essay defends the significance of ethnography for ecclesiology. It does so by engaging with the ecclesiology of John Webster, particularly his essay ‘In the Society of God’, which directly challenges the appropriateness of ethnographic methods for a theology of the church. The discussion demonstrates the importance of Webster’s warning against the reduction of ecclesiology to an uncritical embrace of the apparent ‘givenness’ of empirical observations, but also argues that his approach is less useful for analyzing and criticizing the failures of the church community. The essay concludes by arguing that ethnography has the potential to enhance the church’s capacity to recognise, and thus confess, its sins, but also to deepen its corporate discernment and attentiveness to the presence of God’s activity in its midst.